Welfare state e desenvolvimento - Celia Lessa Kerstenetzky (Universidade do Estado do Rio de Janeiro, 2011)
The relations between the welfare state and development are frequently portrayed as problematic and even dilemmatic. For example, it is claimed that the welfare state is only possible in developed countries, or that typical welfare state redistribution is necessarily accompanied by weaker economic growth. The main purpose of this article is to systematize the arguments and evidence against these assumptions, featuring the functionality of the welfare state for development in both economic and non-economic terms.